Study of Hydrolysis of Mono 2,5-Diethoxy Aniline Phosphate in Acid Medium at Constant Ionic Strength - TANGRI, ALKA; MAURYA, SUMITRA (Asian Journal of Chemistry, 2010)
The present work is focused on the mechanism of hydrolytic break down of mono 2,5-diethoxy aniline phosphate. The phosphate esters find application depending upon the kind of linkages involved. The hydrolysis was carried out at three different temperatures. Ionic strength data and the effect of concentration point to existence of conjugate species of mono 2,5-diethoxy aniline phosphate as reactive species in acid region.